Annie Besant’s Role in India’s Struggle for Independence: Exploring Annie Besant's Multi-Faceted Contribution to India's Freedom Movement and Trans-Cultural Engagement (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The life of Annie Besant (1847– 1933) is set apart by a noteworthy range of commitment which involved various intersections of outskirts and limits outlining social, cultural, ideological, geo-political and sexual orientation refinements. Amid her initial profession she was a noticeable supporter of logic, secularism, women's rights, conception prevention, and socialism. She later swung to Theosophy and settled in India, where she turned into the President of the Theosophical Society and a critical figure in the Indian independence movement. Her life story can to a significant degree be viewed as a self-referential mixing of political, profound and trans-cultural undertakings. While the mix of the political and otherworldly is a component of Besant's life story that is imparted to other contemporary savvy people and pioneers, it picks up an extra many-sided quality as it dove-tails with an express trans-cultural undertaking worried about deciphering thoughts and terms from one culture into another, and proposing it as an answer for what she viewed as an emergency of expansionism and realism, and additionally of old qualities.